2015
DOI: 10.1371/journal.pone.0142847
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine Improves the Efficacy of Nebulized Hypertonic Saline in Moderate Bronchiolitis: A Randomised Clinical Trial

Abstract: Background and AimsThere is no evidence that the epinephrine-3% hypertonic saline combination is more effective than 3% hypertonic saline alone for treating infants hospitalized with acute bronchiolitis. We evaluated the efficacy of nebulized epinephrine in 3% hypertonic saline.Patients and MethodsWe performed a randomized, double-blind, placebo-controlled clinical trial in 208 infants hospitalized with acute moderate bronchiolitis. Infants were randomly assigned to receive nebulized 3% hypertonic saline with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 30 publications
2
15
0
3
Order By: Relevance
“…Of the three trials performed using the nebulization protocol of three doses every 2 h, followed by five doses every 4 h in the first 24 h, then every 6 h until discharge, two resulted in a significant shortening of LOS but one did not . While the intervals between nebulization therapy in the other trials that showed a shortened LOS were every 8 h and every 6 h, the intervals in the trials that did not show any shortening of LOS were every 4 h, every 6 h, and every 8 h . The systematic review showed no significant difference in the reduction of LOS between trials that used more frequent saline nebulization .…”
Section: Discussionmentioning
confidence: 95%
“…Of the three trials performed using the nebulization protocol of three doses every 2 h, followed by five doses every 4 h in the first 24 h, then every 6 h until discharge, two resulted in a significant shortening of LOS but one did not . While the intervals between nebulization therapy in the other trials that showed a shortened LOS were every 8 h and every 6 h, the intervals in the trials that did not show any shortening of LOS were every 4 h, every 6 h, and every 8 h . The systematic review showed no significant difference in the reduction of LOS between trials that used more frequent saline nebulization .…”
Section: Discussionmentioning
confidence: 95%
“…According to a review prepared by Chen et al 21 ; HS significantly decreased both the rate and the duration of hospitalization. A study from Spain has demonstrated that ADR+HS significantly shortens LOS in hospitalized infants with acute moderate bronchiolitis compared to HS 22 . In the study of Miraglia et al 23 ; ADR+HS was found significantly superior to ADR with regard to LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are contrary to those of other reports that show w1-day mean reduction in the duration of hospitalization for children with bronchiolitis using inhaled HS 3,17 or no effect 11e13 of inhaled HS on the LOS. Nevertheless, variability in dosage regimens and cointerventions, 18 as well as no short-term improvement in clinical scores with inclusion of 3% HS in inhaled therapy 19,20 and no additional benefit of adding 3% HS to nebulized solution with bronchodilators, 21 all call into question the beneficial effects of 3% HS. A revised American Academy of Pediatrics clinical practice guideline published in 2014 identified administration of nebulized HS to infants and children hospitalized for bronchiolitis as a weak recommendation due to inconsistent findings.…”
Section: Characteristicsmentioning
confidence: 99%